A carcinicultura familiar na aldeia indígena potiguara de tramataia, marcação - Paraíba: em busca da sustentabilidade - Sampaio, Jeandelynne Araújo de (2015)
The Indigenous Land Potiguara is situated in the north coast of Paraíba, between Camaratuba and Mamanguape rivers, totaling 33,757.00 hectares, of which 1451.20 hectares are overlapping area with the APA of the Mamanguape River Bar, with a population of 19 000 inhabitants. This research aimed to analyze the environmental and social impacts and conflicts after the introduction of shrimp Indigenous Land (TI), from participatory methodology. It can be seen clearly that there are two distinct areas of shrimp farming in the village, one located next to the houses, which have greater influence of non-Indians, increased environmental impacts and are independent families with each other, and another located on the Island of girls with nurseries belonging to the prawn Cooperative Tramataia, only with partners Indians, where there is organization and all pools together belong to all members. According to the Sustainability Framework applied in the two areas, the first has low sustainability, reaching 36.36% positive sustainable responses, while the second reached an average sustainability, reaching 54.55% of positive sustainable questions. So were seen in the first area impacts as mangrove trees cuts, stressed plants, crabs UCAS dead, chemical channels that enter the mangrove, waste coming from the houses and the very exposed activity, in the second area, the worst impact viewed was the proximity of the nurseries with the bank of the estuary of the river Mamanguape. Participatory meeting was organized jointly local wisdom and so was the recognition of all the problems involving the shrimp before an unknown to the Indians. After the technical training person chosen at this meeting, there was the first analysis, independent of outside the village technicians, and through this, the trained Indian identified specific pathology in nursery with early mortality, which was instrumental in making decision and not lost production, avoiding the dead animals were dumped into the estuary. This work is the basis for the implementation of efficient management with dialogue between technical and scientific knowledge and local knowledge and minimize negative impacts, aiming at higher productivity and environmental sustainability.